#TITLE_ALTERNATIVE# - PUTRI PARAMITA (NIM: 20715031), DIAJENG
Pharmaceutical solid dosage forms consist not only one active pharmaceutical ingredient with excipients, but also combination two or more active pharmaceutical ingredients with excipients. Manufacturing of pharmaceutical dosage form involves various energies, such as thermal and mechanic energy and so does the use of certain solvent in each unit process. Energy and solvent exposure can induce interaction between ingredients in the formula. In one component system, the energy can lead to polymorphic transformation and crystallinity change of active pharmaceutical ingredient, while interaction that involves at least two components can generate eutectic reaction, solvate/hydrate formation, and formation of mixed crystal or molecular compound (cocrystal). It has been known that combination sulfamethoxazole and trimethoprim interact to form new crystalline phase. It is cocrystal phase with 1:1 stoichiometry, which is formed under exposure of thermal and mechanic energy and in solvent system. Cocrystal was also reported to be formed upon high humidity due to induction of adsorbed water vapor on particlesÃ‚Â’ surfaces. Kinetic of cocrystal formation has been studied using powder X-ray diffraction method. Equimolar mixture (1:1) of cocrystal-forming components, sulfamethoxazole and trimethoprim, was injected into heating process in three different temperatures: 160, 165, and 170C. The heating was conducted isothermally for fifty minutes with sampling at minute 5, 10, 30, 40, and 50. Quantitative analysis was performed by internal standard method. Basically, the sample is doped with a known amount of material referred as internal standard and intensity ratio of diffraction peak of analyte phase to be analyzed (IS) against of internal standard (II) is used to calculate the amount of analyte within the sample. Calibration curve was obtained from mixture of cocrystal phase prepared from solvent evaporation method with equimolar physical mixture of sulfamethoxazole-trimethoprim and cocrystal phase within the mixture has been determined. Potassium chloride (KCl) (25%, w/w) was added into the samples as internal standard material. Calibration curve was plotted from cocrystal composition versus IS/II ratio and exhibited good linearity with correlation coefficient of 0,9962 and regression line was obtained y = -0,1286 + 1,1895x. The rate of formation was described by order of reaction model. Determination of order of reaction showed that cocrystal formation kinetic upon heating followed zero-order.